Komodifikasi Al-Quran - Nor Lutfi Fais (MAGHZA, 2021)
Religion commodifications, including the issue of the Quran, are not a real breakthrough in socio-religious studies. Various studies have been carried out. However, the current studies are still limited to descriptions of the variety of commodification and problems that occur and have not reached yet the aspect of dismantling the social intrigues in them. For this reason, this study intends to read the commodification of the Quran as a social phenomenon and at the same time expose the hidden aspects in it. This study uses the social theory of The Consumer Society, initiated by Jean Baudrillard which includes aspects of commodification, media shaping, and social shifting paradigm: needs towards desires and lifestyles, by adopting relevant disciplines of the Quran such as riwayat, qira ah and tajwid. The object to be studied is Mushaf Al-Quran Grand Maqamat or known as Al-Quran Digital Talking Pen Grand Maqamat. After conducting the study, it was found that the commodification of the Quran that occurred was part of the industrialization effort of the Qur’an by using religious actors as an excuse and as a marketing medium. Commodification that occurs is also not in line with the spirit of necessity which refers to the concepts of riwayat, qira ah and tajwid in the Quran.